Tacrolimus can induce remission in cyclosporine and mycophenolate mofetil resistant pediatric onset nephrotic syndrome (Iranian Journal of Kidney Diseases, 2019)
Nephrotic syndrome (NS) is one of the commonest pediatric renal disorders. Most of these patients are steroid responsive. About 10%–20% of children with new onset NS are resistant to steroid treatment. Patients who are resistant to steroids have limited treatment options such as calcineurin inhibitors (CNIs), mycophenolate mofetil (MMF) and rituximab. Despite several studies had documented that tacrolimus is superior to cyclosporine A (CsA) and MMF in treating SRNS but there are no studies on the efficacy of tacrolimus in treating CsA and MMF resistant NS in pediatric populations. Study objective was to evaluate the role of tacrolimus in treating refractory idiopathic nephrotic syndrome .One hundred-twenty patients with idiopathic nephrotic syndrome were included in the study. Patients with steroid resistant NS were given cyclosporine (CsA) (first step protocol). In patients with cyclosporine resistant NS a combination of CsA+ MMF was given as a second step protocol. Unresponsive patients received tacrolimus as a third step treatment protocol. Tacrolimus was given at a starting dose of 0.1mg/kg/day then the dose was modified according to serum trough levels and patients were followed up for 12 months to evaluate the outcome. Out of 120 patients, 15 were both cyclosporine and MMF resistant and received tacrolimus. Tacrolimus had induced remission in 11 (73.3%) patients during the 1st 6 months of therapy. Eight patients achieved complete remission and three patients had partial remission.Conclusions: Tacrolimus is effective in treating refractory multi-drug resistant NS with favorable outcomes in childhood onset NS.